On ?-convergence and ?-boundedness of mth order - Ercan, Sinan; Asma Bektas, Cigdem (Taylor & Francis Inc, 2021)
In the present paper, we introduce the notion of lambda(m)-convergence and lambda(m) -boundedness. We examine the relationship of these notions between of the ordinary convergence and ordinary boundedness, respectively. We also introduce new sequence spaces and some topological properties of these spaces. Furthermore, we investigate some inclusion relations between these sequence spaces and other well known sequence spaces.
Keywords: BK-spaces; Schauder basis; sequence spaces